Probiotics-Based Treatment as an Integral Approach for Alcohol Use Disorder in Alcoholic Liver Disease - Fuenzalida, Catalina; Dufeu, María Soledad; Poniachik, Jaime; Roblero, Juan Pablo; Valenzuela-Pérez, Lucía; Beltrán, Caroll Jenny (Frontiers in Pharmacology, 2021)
Alcoholic liver disease (ALD) is one of the leading causes of morbidity among adults with alcohol use disorder (AUD) worldwide. Its clinical course ranges from steatosis to alcoholic hepatitis, progressing to more severe forms of liver damage, such as cirrhosis and hepatocellular carcinoma. The pathogenesis of ALD is complex and diverse elements are involved in its development, including environmental factors, genetic predisposition, the immune response, and the gut-liver axis interaction. Chronic alcohol consumption induces changes in gut microbiota that are associated with a loss of intestinal barrier function and inflammatory responses which reinforce a liver damage progression triggered by alcohol. Alcohol metabolites such as acetaldehyde, lipid peroxidation-derived aldehyde malondialdehyde (MDA), and protein-adducts act as liver-damaging hepatotoxins and potentiate systemic inflammation. Additionally, ethanol causes direct damage to the central nervous system (CNS) by crossing the blood-brain barrier (BBB), provoking oxidative stress contributing to neuroinflammation. Overall, these processes have been associated with susceptibility to depression, anxiety, and alcohol craving in ALD. Recent evidence has shown that probiotics can reverse alcohol-induced changes of the microbiota and prevent ALD progression by restoring gut microbial composition. However, the impact of probiotics on alcohol consumption behavior has been less explored. Probiotics have been used to treat various conditions by restoring microbiota and decreasing systemic and CNS inflammation. The results of some studies suggest that probiotics might improve mental function in Alzheimer's, autism spectrum disorder, and attenuated morphine analgesic tolerance. In this sense, it has been observed that gut microbiota composition alterations, as well as its modulation using probiotics, elicit changes in neurotransmitter signals in the brain, especially in the dopamine reward circuit. Consequently, it is not difficult to imagine that a probiotics-based complementary treatment to ALD might reduce disease progression mediated by lower alcohol consumption. This review aims to present an update of the pathophysiologic mechanism underlying the microbiota-gut-liver-brain axis in ALD, as well as to provide evidence supporting probiotic use as a complementary therapy to address alcohol consumption disorder and its consequences on liver damage.